2018
DOI: 10.1002/admi.201701113
|View full text |Cite
|
Sign up to set email alerts
|

Origami‐Inspired 3D Interconnected Molybdenum Carbide Nanoflakes

Abstract: COMMUNICATION (1 of 7)the energy requirements of the world. However, with the increase of population and development of technology, fossil fuels cannot serve as the primary energy source in the future due to the shortage of energy resources and a series of environment problems. As a result, renewable energy sources and their storage are becoming increasingly important. To solve this energy demand, it is necessary to develop new systems to improve the efficiency of energy conversion and storage. Development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The structure information was further obtained by Raman and N 2 ad‐/desorption analysis.As shown in Figure g, the peaks centred at 818 and 992 cm −1 for nanotablets material confirm the formation of Mo 2 C, and the broad shoulder peaks located at ca. 1350 cm −1 and 1590 cm −1 are magnified and displayed in inset of Figure g, which are matched to the D and G bands originated from the defective carbon and graphitic carbon, respectively . The intensity ratio of 0.89(I D /I G ) shows the high degree of graphitization in Mo 2 C/C nanotablets material.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The structure information was further obtained by Raman and N 2 ad‐/desorption analysis.As shown in Figure g, the peaks centred at 818 and 992 cm −1 for nanotablets material confirm the formation of Mo 2 C, and the broad shoulder peaks located at ca. 1350 cm −1 and 1590 cm −1 are magnified and displayed in inset of Figure g, which are matched to the D and G bands originated from the defective carbon and graphitic carbon, respectively . The intensity ratio of 0.89(I D /I G ) shows the high degree of graphitization in Mo 2 C/C nanotablets material.…”
Section: Methodsmentioning
confidence: 96%
“…1350 cm À 1 and 1590 cm À 1 are magnified and displayed in inset of Figure 1g, which are matched to the D and G bands originated from the defective carbon and graphitic carbon, respectively. [32,33] The intensity ratio of 0.89(I D / I G ) shows the high degree of graphitization in Mo 2 C/C nanotablets material. Itsmesoporous-structure characteristicis observed from N 2 ad/desorption curve ( Figure 1h) and the pore size distribution isin the range of 2-4 nm (inset in Figure 1h), indicating successful synthesis of mesoporous Mo 2 C material possessing hexagonaltablet morphology.…”
mentioning
confidence: 98%
“…The structure-directing method of molybdenum carbide particle preparation may involve other groups of organic precursors such as dyes [114], saccharides [115,116], chelates [117], urea [118,119], metal-organic frameworks [120], polymers (polyaniline, polypyrrole) [121], and volatile organic compounds (VOCs) [122]. Recently, Gavrilova et al [123] reported a Mo 2 C preparation method via thermal decomposition of molybdenum blue nanoparticles.…”
Section: Structure-directing Methodsmentioning
confidence: 99%
“…In Table 6, selected methods for molybdenum carbide preparation using the structure-directing method are summarized. Koizumi et al [122] reported the synthesis of interconnected molybdenum carbide phase nanoflakes that form 3D origami-like structures. The methods for preparation of the structures involved chemical vapor deposition (CVD).…”
Section: Structure-directing Methodsmentioning
confidence: 99%
“…[14,15] TMCs also exhibit superior electrical conductivities and broader pH applicability when compared with TM oxides/sulfides/phosphides/nitrides. [16,17] In these regards, the kinetics of HER on the TMCs has been much boosted or the HER performance on the TMCs is outstanding (e.g., high catalytic activity and long-term stability). Unfortunately, the density of empty d-bands in most TMCs is high, results in the strong binding of a TMC electrocatalyst with hydrogen intermediate (H*).…”
Section: Introductionmentioning
confidence: 99%